FACTORS AFFECTING STUDENTS’ INTENTION TO DROPOUT FROM UNIVERSITY - Thanaletchumi Letchumanan; Kogilavani Apadore; Noor Azizah Shaari; Lim Zhi Yue; Liyaarni Nair a/p K.Asokan; Mathupriya a/p Selvaraj; Tou Wei Siong (Journal of Islamic, Social, Economics and Development, 2024)
While the higher education sector is expanding, student dropout has always been an issue in many areas, to the point that it is at an alarming rate. Therefore, this study aims to determine the main factors that bring significant impact towards students’ intention to dropout from university. 3 major factors have been selected in order to examine the degree of impact towards intention to dropout: sense of belonging, academic difficulty and ability, external influences. The sampling technique employed is convenience sampling. A questionnaire that consists of 24 questions related to the major factors was distributed and 377 responses were collected. The major findings of the analysis are: (1) Sense of belonging has a significant impact with the intention to dropout among university students. (2) Academic difficulty and ability have a significant impact with the intention to dropout among university students. (3) External influences do not have significant impact with the intention to dropout among university students. Hence, it is recommended that policymakers should craft policies that can aid students’ need of belonging and academic difficulty and ability in order to reduce dropout rate.